2000
DOI: 10.1016/s0082-0784(00)80355-0
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of fullerenes and fullerenic nanostructures in a low-pressure benzene/oxygen diffusion flame

Abstract: Samples of condensable material from laminar low-pressure benzene/argon/oxygen diffusion flames were collected and analyzed by high-performance liquid chromatography to determine the yields of fullerenes and by high-resolution transmission electron microscopy (HRTEM) to characterize the fullerenic material (i.e., curved-layer nanostructures) on and within the soot particles. The highest concentration of fullerenes was always detected just above the visible stoichiometric surface of a flame. The percentage of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 23 publications
1
28
0
Order By: Relevance
“…These two parameters are both correlated to chamber pressure, argon dilution, and cold gas fuel velocity. Typical fullerene yields of 0.5% (by mass) of total carbon fed were observed but can possibly be higher [90,91].…”
Section: Methods Ofproductionmentioning
confidence: 99%
See 3 more Smart Citations
“…These two parameters are both correlated to chamber pressure, argon dilution, and cold gas fuel velocity. Typical fullerene yields of 0.5% (by mass) of total carbon fed were observed but can possibly be higher [90,91].…”
Section: Methods Ofproductionmentioning
confidence: 99%
“…The premixed study also found that nanostructures require a much longer residence time to form than do fullerenes [37]. The diffusion flame analysis showed that nanostructures are formed higher than the point of maximum fullerene production where soot and fullerenes are being consumed by oxidation and the flame is the hottest [90,91]. Additionally, structures similar to those observed in fullerene-forming flames have also been found in commercially-produced carbon black [100,101].…”
Section: Nanostructureformation Inflamesmentioning
confidence: 96%
See 2 more Smart Citations
“…27.1 ) and technological. Note that direct synthesis of fullerenes from benzene is carried out in fl ame jet at benzene combustion at defi cit of oxygen and at low pressure [ 7,8 ] .…”
Section: Introductionmentioning
confidence: 99%